Population genetic structure and demographic history of the spadefish, Chaetodipterus faber (Ephippidae) from Southwestern Atlantic - Machado, Leonardo Francisco [UNESP]; Damasceno, Junio de Souza; Bertoncini, Athila Andrade; Tosta, Vander Calmon; Cazerta Farro, Ana Paula; Hostim-Silva, Mauricio; Oliveira, Claudio [UNESP] (Elsevier B.V., 2017)
Genetic diversity, population structure and demographic history of Chaetodipterus faber in SW Atlantic were investigated using mitochondrial DNA cytochrome c oxidase subunit 1(620 bp) and D-loop (817 bp) sequences. Individuals were collected in five sampling units (SUs) located in latitudes between 2 degrees S and 27 degrees S, southernmost limit of species distribution. The COI sequences from Brazilian sampling units were compared with eight sequences from the Gulf of Mexico and Caribbean, resulting in no significant genetic differences (K2P < 0.32%). On the contrary, pairwise F-ST analysis based on D-loop datasets from the five SUs indicated divergence between Tropical and Subtropical clades of SW Atlantic C. faber. The SAMOVA approach was consistent with this divergence and revealed maximal variance among groups (63.59%) when two clades are simulated (k = 2), setting apart Tropical and Subtropical SUs. Demographic analyses support the hypothesis of population expansion, both for Tropical and Subtropical clades. Moreover, Subtropical population size increase was dated after the Tropical clade reached the demographic stability, around 10 kyr ago, during the beginning of interglacial Pleistocene Holocene transition. The historical demographic results, along with the lower genetic diversity and the star shaped haplotype network of the Subtropical clade corroborate an ancient scenario of the species' adaptive radiation southward. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Population genetics; Reef fishes; D-loop; COI; Haplotypes; SW Atlantic